The dynamic analysis of elastic elements of condensing devices of pneumolifting installations at skip movement - Aikeyeva, A.A. (Publishing House of the KarSU named after E.A.Buketov, 2013)
Modern information methods are based on the system analysis and consider peculiarities of manufacturing techniques and operation on the basis of car modelin. Their realizations are by methods of nonlinear mechanics of deformation and destruction. In this regard, application of these methods to calculation of lifting vessels (skips) of mine and opencast pneumolifting installations is an actual problem of ensuring reliability of their work, experimental check of the results obtained by theoretical way. Besides, modern theoretical methods of calculation and design of various products and constructions assume active use of the method of the final elements possessing concentrated expression that is the package of the applied ANSYS programs. In this plan the package of the applied ANSYS programs can be used at theoretical and analytical researches as well.
Keywords: mine skip; elastic; elements; pneumolifting; installations; nonlinear; deformation